PEMANFAATAN MEDIA PEMBELAJARAN IPS TERHADAP PENCAPAIAN HASIL BELAJAR SISWA - man, Herman man (Makassar Journal of Social Sciences, 2013)
This study aims to investigate the influence of media use and learning social studies student achievement in SMP Negeri 3 Marioriawa. As well as to determine the presence or absence of a relationship between the use of media influence on the achievement of learning social studies students in Junior High School beajar 3 Marioriawa.The study was conducted with descriptive quantitative statistical approach. The variables consisted of the use of instructional media (variable X ) and learning outcomes (Y ). The population of this study were students of SMP Negeri 3 Marioriawa much as 134 people as well as a sample of class VIII as many as 33 people. The data collection technique is observation , questionnaires , and documentation . Data analysis techniques performed by descriptive statistical analysis and statistical analysis infrensial . Based on the research results can be seen that illustrates the effect of the use of instructional media in the category of " very good " and a picture of student learning outcomes fall into the category of " good ". And there is a relationship between the use of instructional media for improving student learning outcomes in SMP Negeri 3 Marioriawa